2021
DOI: 10.1083/jcb.202007149
|View full text |Cite
|
Sign up to set email alerts
|

RTKN-1/Rhotekin shields endosome-associated F-actin from disassembly to ensure endocytic recycling

Abstract: Cargo sorting and the subsequent membrane carrier formation require a properly organized endosomal actin network. To better understand the actin dynamics during endocytic recycling, we performed a genetic screen in C. elegans and identified RTKN-1/Rhotekin as a requisite to sustain endosome-associated actin integrity. Loss of RTKN-1 led to a prominent decrease in actin structures and basolateral recycling defects. Furthermore, we showed that the presence of RTKN-1 thwarts the actin disassembly competence of UN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…However, the mechanism controlling the localization of SMAPs is still not well understood. Here, by using a well-established in vivo membrane trafficking investigation model ( Chen et al, 2018 ; Chen et al, 2019 ; Gao et al, 2020 ; Zhang et al, 2020 ; Yan et al, 2021 ), we showed that the integrity of AP-1 adaptor is necessary for the TGN positioning of SMAP-1. Although we did not specifically identify which AP-1 subunit governs the TGN localization of SMAP-1, our results suggested that in addition to CALM, SMAP-1 underlies an additional clathrin assembly mechanism, enriching the understanding of AP-1/clathrin coat assembly.…”
Section: Discussionmentioning
confidence: 89%
“…However, the mechanism controlling the localization of SMAPs is still not well understood. Here, by using a well-established in vivo membrane trafficking investigation model ( Chen et al, 2018 ; Chen et al, 2019 ; Gao et al, 2020 ; Zhang et al, 2020 ; Yan et al, 2021 ), we showed that the integrity of AP-1 adaptor is necessary for the TGN positioning of SMAP-1. Although we did not specifically identify which AP-1 subunit governs the TGN localization of SMAP-1, our results suggested that in addition to CALM, SMAP-1 underlies an additional clathrin assembly mechanism, enriching the understanding of AP-1/clathrin coat assembly.…”
Section: Discussionmentioning
confidence: 89%
“…119 A recent study identified RTKN-1/ Rhotekin, an effector of the Rho GTPase, as a new molecule necessary for endosomal recycling via the regulation of endosome-associated F-actin structures in the intestine of C. elegans. 122 Interestingly, targeting of RTKN-1 to endosomes appears to depend on SDPN-1, stressing out the importance of SDPN-1 for the normal physiology of the intestine in worms via the intertwined functions of endosomal recycling and actin cytoskeleton. 122 Another level of regulation for SDPN-1 is brought by phosphoinositides, and specifically, phosphoinositide PI(4,5)P2.…”
Section: Elegansmentioning
confidence: 97%
“…122 Interestingly, targeting of RTKN-1 to endosomes appears to depend on SDPN-1, stressing out the importance of SDPN-1 for the normal physiology of the intestine in worms via the intertwined functions of endosomal recycling and actin cytoskeleton. 122 Another level of regulation for SDPN-1 is brought by phosphoinositides, and specifically, phosphoinositide PI(4,5)P2. PI(4,5)P2 plays a central role in endosomal recycling 123 and interestingly, in C. elegans with mutated Arf-6 and CNT-1, also known to regulate endosomal recycling, the expression of SDPN-1 was altered in the intestinal basolateral recycling endosomes due to changed concentrations of PI (4,5)P2 in this location.…”
Section: Elegansmentioning
confidence: 97%
See 2 more Smart Citations